An Analysis of Households’ Demand for Improved Solid Waste Management in Birendranagar Municipality, Nepal - Bhattarai, Kumar; Pathak, Balaram; K.C., Binod (International Journal of Energy Economics and Policy, 2017)
There is rapid urbanization in Birendranagar municipality. Due to which, the municipality is facing the problem of solid waste management. If the solid waste is not managed properly on time, it may create problem on human health and environment. This study was designed to estimate the households’ willingness to pay for improved solid waste management in Birendranagar municipality, Nepal. To elicit the willingness to pay, single-bounded dichotomous choice contingent valuation method was employed. Study was based on cross-sectional survey of, randomly selected, 300 households. Out of total respondents, 91.33 percent respondents were interested for the improved solid waste management service offered whereas 51.67 percent respondents were willing to pay for offered bid amounts. The mean willingness to pay was Rs 90.12 per household per month. Result reveals that bid amount, level of education, present waste collection service and level of income are the factors determining the households’ willingness to pay for the improved solid waste management in Birendranagar municipality. Currently, municipality is not charging for the solid waste collection service and the private service provider is charging Rs 50 per household per month. Thus, present garbage fee is far below the mean willingness to pay of households. So, there is the opportunity of collecting sufficient funds for the provision of better solid waste management service in the municipality. Keywords: Birendranagar municipality, Dichotomous choice, Single-bounded contingent valuation method, Willingness to pay, Solid waste management JEL Classifications: Q5, R2